Tala learns to siva - Netane, Kealani (Orchard Books, an imprint of Scholastic Inc., 2024)
"Learning to siva from the heart... Tala loves watching her Aunty Sina's graceful steps in the taualuga, a traditional Samoan dance, where her hands curl like rolling waves and her feet glide across the floor like canoes. Yet when Tala tries to siva, her legs are too wobbly, her arms are too stiff, and most of all, she doesn't have the same glow as when Aunty dances. Tala tries to muster the courage to perform at her Grandma's birthday. But she freezes on stage. Will she find the strength and inspiration to help her dance? Kealani Netane's glowing debut picture book is a relatable tale of a young girl finding her own rhythm through the love and guidance of her family. Meanwhile New York Times bestselling illustrator, Dung Ho's cheerful, lush art creates a spellbinding trance that will inspire readers to get up and siva"--